Implementation of Work Safety for Crew on MV. Ibrahim Zahier: Penerapan Keselamatan Kerja untuk Anak Buah Kapal di MV. Ibrahim Zahier - Baihaqi, Baihaqi; R., Sulastriani; Nurmala, Eka; Sabaruddin, Sabaruddin; Purba, Bulan Hadi (ALTAIR: Jurnal Transportasi dan Bahari, 2024)
Safety at sea is a top priority in the maritime industry. Accidents can occur on land or aboard ships, often due to negligence regarding safety protocols. An analysis of accidents reveals that each incident has a causal factor. Ship operations involve various tasks, both light and heavy, which pose risks to crew safety. This study employs a qualitative methodology, utilizing direct observation of the ship and conducting interviews to gather necessary research data, along with reading and referencing various materials. The findings of this study are as follows: 1) Accidents involving crew members often result from failing to adhere to established safety standards, specifically, those outlined in the Safety Management System (SMS) on the ship; 2) The consequences of such accidents can include eye infections caused by rust or corrosion fragments entering the eyes. Affected crew members must receive special treatment on land after initial care is provided by the 2nd officer, which includes rinsing the eyes with an eyewash solution; and 3) To improve safety for the crew, the Captain should instruct all crew members to review the procedures outlined in the Safety Management System (SMS) regularly. Additionally, the Captain should emphasize these procedures during meetings and actively monitor any potentially hazardous work activities.